Microstructural characterization of ti-6al-4v with different chemical etching reagent - Goh, XiuMing (2018)
The application of titanium and its alloys particularly Ti-6Al-4V has been increasing over the last few decades due to the attractive combination of its high strength and low density characteristic. With the superior properties, it is unquestionably that Ti-6Al-4V is most notably used in the aerospace industry. As such, it has drawn interest to characterize the material using a newly developed technique, directional reflectance microscopy (DRM), an advanced optical microscopy technique which quantifies grain reflectance in optical micrographs as a function of the surface structures of materials. As mentioned that DRM is a relatively new characterization technique, hence in this study the goal is to investigate the suitability of DRM to study Ti-6Al-4V. Prior to that, the samples’ cross-sectional surfaces were prepared to optimum state and chemically etched by Kroll’s and Keller’s reagents respectively. By doing so, we could study the effects of different chemical etching reagents it has on Ti-6Al-4V, leading to identify the suitable one for quantifying the grain reflectance using DRM. The effects of different etchants were observable from the contrast of grains presented in the optical micrographs, that being so it influenced the grain reflectance as well. Following that, the reflectance of a selected grain can be visualized from the directional reflectance profiles (DRPs), which is obtained from the MATLAB program. With comparisons made between etchants, Kroll’s reagent is evidently a preferred chemical etchant for Ti-6Al-4V as it enables the observations of distinct grains contrast presented on gain reflectance map, subsequently the analysis of data return with positive results that deem the potential to infer beneficial crystallography information with DRM technique.